Exposure of Contralateral Eyes to Laser Radiation during Retinal Photocoagulation. (2nd September 2021) - Gauldin, Donald; Ahmad, Kinza T; Ferguson, Scott; Uwaydat, Sami H
ABSTRACT: Purpose/Aim : To investigate the risk of laser damage to the unprotected fellow eye of patients undergoing laser retinal photocoagulation with 532 nm diode pumped solid-state laser. Materials and Methods : A mannequin head was fitted with a Vega laser energy meter and PD10 photodiode laser measurement sensor. Lowest measurable energy for this sensor is 2 nJ at 900 nm. Simulated retinal laser treatments were performed on a model eye placed in one of the sockets of the mannequin head, while the laser sensor was placed in the opposite socket. Four simulated sessions of retinal photocoagulation were performed utilizing both slit lamp and indirect laser delivery systems. Each consisted of 10 applications of the laser directly into the model eye and 10 applications near but not directly into the sensor, utilizing various treatment settings. Results : No laser exposure was detected in the model eye during simulated retinal photocoagulation sessions aimed directly into the treatment eye. When the laser application was aimed near the sensor, no laser exposure was detected at the standard setting, however, in all sessions conducted at the higher laser power setting, the mean exposure detected was <6 µJ Conclusions : Laser exposure in the unprotected contralateral eye of patients undergoing retinal laser treatment with the PASCAL laser machine under standard PRP settings was found to be miniscule. However, we still recommend laser safety eyewear for the untreated eye to provide protection in the event of direct accidental laser exposure from surgeon error or laser malfunction, in accordance with the most current laser safety guidelines.